The Feminist Voice in Mainstream News Discourse - (:unkn) unknown (My University, 2016)
This thesis analyzes the work of six self-identified feminist women who wrote opinion pieces for mainstream news and cultures sites in 2014. The internet and the widening public sphere has opened up new spaces for feminist writing that has allowed this writing to be published and read on a large and easily accessible platform. This group of women is an example of a broader generational development born out of third wave feminism, postfeminism, and the rise of online platforms for political commentary. By introducing traditionally private matters into the public sphere, their columns challenge dominant cultural discourse about political issues that are important to women. Further, their work highlights the problematic nature of the internet as a public sphere. Through the creation of columns that are a combination of feminist blogging and political commentary, their work represents a change in traditional mainstream news discourse.
Keywords: Digital Culture; Digital News; Feminism; Feminist Writing; Mainstream Media; Opinion Writing